Manajemen Keuangan Pondok Pesantren Berbasis PSAK No. 45 - Mariyah Ulfah; Ayus Ahmad Yusuf (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
This study aims to analyze the financial management practices at Pondok Pesantren Al Murtadlo Buntet and their compliance with the Indonesian Financial Accounting Standards Statement (PSAK) No. 45 on Nonprofit Entity Financial Reporting. Using a descriptive qualitative approach and case study method, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the pesantren’s financial management is still simple, limited to recording cash inflows and outflows, and has not yet presented the four main reports required by PSAK No. 45, namely the statement of financial position, statement of activities, cash flow statement, and notes to the financial statements. The main challenges include limited human resources, lack of accounting knowledge, traditional administrative culture, and absence of supporting infrastructure. Nevertheless, the implementation of PSAK No. 45 is considered capable of enhancing transparency, accountability, public trust, and opening opportunities for external collaboration. This study also proposes a three-stage roadmap for implementing PSAK 45: short-term (awareness building and asset inventory), medium-term (system strengthening and internal audits), and long-term (professionalization and financial digitalization). The study concludes that the application of PSAK No. 45 at Pondok Pesantren Al Murtadlo Buntet is a strategic necessity to strengthen modern and professional financial governance while preserving the pesantren’s identity as an Islamic educational institution based on sincerity.